2019
DOI: 10.18805/ijare.a-5288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Defoliants on Yield and Fibre Quality of American Cotton in Semi-Arid Conditions

Abstract: The study was conducted for exploring the effect of Dropp ultra and Ethrel, their application rates and time of application on two American cotton cultivars. The experiment was carried out at Regional Agricultural Research Station, Nandyal with cultivars NH615 and Sivanandi for two consecutive seasons from 2015-2017 in split plot design with three replications. Application of defoliants like Dropp ultra SC (Thidiazuron 360 + Diuron 180) 200 and 250 ml/ha, Ethrel 1500, 2000 and 3000 ppm were carried at 120 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…At 15 days after defoliants spray Thidiazuron + Diuron (0.03%) recorded higher defoliation (98.6, 98.1 and 97%) in all three time of application which is on par with Sodium chlorate (0.9%). Similar results were observed in [14] and [15] found the highest defoliation rate in Drop Thidiazuron + diuron treated plants. It might be due to the change of the ethylene to auxin ratio, leaf abscission prematurely occurred after application of defoliants like Thidiazuron [16].…”
Section: Effect Of Defoliants On Defoliation Percentagesupporting
confidence: 91%
“…At 15 days after defoliants spray Thidiazuron + Diuron (0.03%) recorded higher defoliation (98.6, 98.1 and 97%) in all three time of application which is on par with Sodium chlorate (0.9%). Similar results were observed in [14] and [15] found the highest defoliation rate in Drop Thidiazuron + diuron treated plants. It might be due to the change of the ethylene to auxin ratio, leaf abscission prematurely occurred after application of defoliants like Thidiazuron [16].…”
Section: Effect Of Defoliants On Defoliation Percentagesupporting
confidence: 91%
“…Defoliation initiated from 4 days after defoliant application, Thidiazuron + Diuron (0.03%) treatment registered significantly higher defoliation percent (66.82, 33.02 and 61.90%) at three different stages. Raghavendra et al, (2020) reported that higher leaf defoliation was observed in Dropp ultra @ 200ml/ha spraying. But interestingly, defoliants spray at 120 and 134 DAS recorded the highest defoliation rate.…”
Section: Effect Of Defoliants On Percent Defoliationmentioning
confidence: 98%
“…However, in India, the usage of defoliants could not be exploited much primarily due to their limited availability. However, recent works (Mrunalini et al, 2019 andRaghavendra et al, 2020) Impact of Chemical Defoliants on Chlorophyll Fluorescence, Biochemical Parameters, Yield and Fiber Quality... reported the effect of few defoliants on upland cotton in India. With these background, an experiment was conducted to study the impact of defoliants on improving defoliation capacity in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…A two-year study conducted on black cotton soil at Nandyal, Andhra Pradesh with American cotton under semi-arid conditions revealed that significantly higher defoliation percentage was observed with defoliant spray at 140 DAS (92.2 %) compared to defoliant application at 120 DAS (87.2%) (Raghavendra and Rama Reddy, 2020). Gormus et al, (2017) Mrunalini et al, (2019) from Bapatla, Andhra Pradesh reported that net returns (Rs.…”
Section: Percent Defoliation In Cottonmentioning
confidence: 99%